Presence of an interferon signature in individuals who are anti-nuclear antibody positive lacking a systemic autoimmune rheumatic disease diagnosis - Wither, Joan; Johnson, Sindhu R.; Liu, Tony; Noamani, Babak; Bonilla, Dennisse; Lisnevskaia, Larissa; Silverman, Earl; Bookman, Arthur; Landolt-Marticorena, Carolina (Arthritis research & therapy, 2017)
Background Elevated levels of type I interferons (IFNs) are a characteristic feature of the systemic autoimmune rheumatic diseases (SARDs) and are thought to play an important pathogenic role. However, it is unknown whether these elevations are seen in anti-nuclear antibody–positive (ANA + ) individuals who lack sufficient criteria for a SARD diagnosis. We examined IFN-induced gene expression in asymptomatic ANA + individuals and patients with undifferentiated connective tissue disease (UCTD) to address this question. Methods Healthy ANA − control subjects and ANA + titre (≥1:160 by immunofluorescence) participants meeting no criteria, meeting at least one criterion (UCTD) or meeting SARD classification criteria were recruited. Whole peripheral blood IFN-induced and BAFF gene expression were quantified using NanoString technology. The normalized levels of five IFN-induced genes were summed to produce an IFN5 score. Results The mean IFN5 scores were increased in all ANA + participant subsets as compared with healthy control subjects. We found that 36.8% of asymptomatic ANA + and 50% of UCTD participants had IFN5 scores >2 SD above the mean for healthy control subjects. In all ANA + subsets, the IFN5 score correlated with the presence of anti-Ro/La antibodies. In the asymptomatic ANA + subset, this score also correlated with the ANA titre, whereas in the other ANA + subsets, it correlated with the number of different ANA specificities. Development of new SARD criteria was seen in individuals with normal and high IFN5 scores. Conclusions An IFN signature is seen in a significant proportion of ANA + individuals and appears to be associated with ANA titre and type of autoantibodies, rather than with the presence or development of clinical SARD symptoms.